Ekonomi Politik Perminyakan Indonesia: Analisis Kebijakan Liberalisasi Sektor Hulu Migas Indonesia pasca-1998 - Ahmad Rizky Mardhatillah Umar (Jurnal Ilmu Sosial dan Ilmu Politik, 2012)
In the early of 2012, The Government of Indonesia launched a policy proposal remove fuel price subsidy and raise its price up to Rp 6.000. This proposal was followed by mass protests from student, labor, and civil society movement in many provinces. These protest, which was supported by opposition party in parliament (PDIP, Gerindra, and Hanura), ended up with a political compromy at the House of Representative plenary session: The government has opportunity to adjust fuel prices with ‘international oil price’ of Indonesian Crude Price (ICP) rises or falls around 15% in 6 months. Why do the fuel pricing scheme become very dependent with international oil price which is very oligopolistic (Berger dkk, 1988)? Is it a part of the oligarchy consolidation in Indonesia (Robison dkk, 2004)? This paper will try to answer this question by analyzing the political economy of Post-1998 Indonesian oil sector management.